Determinasi Loyalitas Karyawan Pada PDAM Tirtanadi Cabang Medan - Fanny Nadira Siregar (Cattleya Darmaya Fortuna, 2022)
This study aims to determine the effect of individual characteristics, job characteristics, company characteristics and work experience on employee loyalty partially. To determine the effect of individual characteristics, job characteristics, company characteristics and work experience on employee loyalty simultaneously at PDAM Tirtanadi Medan Head Office. The total population in this study amounted to 119 people as a sample using a saturated sampling technique. The analysis technique used is multiple linear regression. The results showed that individual characteristics had a positive and significant effect on employee loyalty, job characteristics had a negative and insignificant effect on employee loyalty, company characteristics had a positive and significant effect on employee loyalty, work experience had a positive and significant effect on employee loyalty. Individual characteristics, job characteristics, company characteristics and work experience have a positive and significant impact on employee loyalty